Association of Inherited Thrombophilia with Recurrent Pregnancy Loss in Palestinian Women - N. S. Abu-Asab; S. K. Ayesh; R. O. Ateeq; S. M. Nassar; W. A. EL-Sharif (Hindawi Limited, 2011)
Objective. This study aimed at analyzing the association between recurrent pregnancy loss (RPL) and factor V G1691A (FVL), prothrombin G20210 (FII); and MTHFR C677T (MTHFR) in Palestinian women. Method. We studied 329 Palestinian women with RPL and/or stillbirth (SB); and compared them to 402 healthy reproductive Palestinian women. Cases and controls were tested for the above mutations. Odds ratio (OR) at confidence interval (CI) of 95% was used as a measure of association between the mutations and RPL. Results. Our statistical analysis showed a slightly increased association, which was not significant between FVL and RPL (OR 1.32, 95% CI 0.90-1.94), and no association between FII (OR 0.84, 95% CI 0.38-1.92), MTHFR (OR 0.58, 95% CI 0.32-1.03), and RPL. Further analysis of RPL subgroups revealed an association between FVL and first-trimester loss (OR 1.33, 95% CI 0.892-1.989), and second-trimester loss (OR 1.13, 95% CI 0.480-2.426), both were not statistically significant. Furthermore, the only statistically significant association was between FVL and SB (OR 2.0, 95% CI 1.05-3.70). Conclusion. Our analysis had failed to find a significant association between FVL, FII, MTHFR; and RPL in either the first or second trimester. FVL was significantly associated with fetal loss if the loss was a stillbirth.